In too deep [compact disc, unabridged] - Child, Lee; Child, Andrew, 1968- (Child, Lee. Jack Reacher novel., 2024)
Reacher wakes up, alone, in the dark, handcuffed to a bed in a makeshift hospital room. His few possessions are gone. He has no memory of getting there. The last thing he can recall is the car he had hitched a ride in getting run off the road. The driver was killed. The people who staged the attack assume Reacher was the driver's accomplice and patch up his wounds as they plan to make him talk. A plan that will backfire spectacularly.